Initiation of pharmacist–psychiatrist collaborative patient education in ambulatory care settings of a tertiary care teaching hospital in south India - Sai Krishna Gudi, Ambed Mishra, Tony David Kurian, Sravani Alla, Justin Kurian, Madhan Ramesh, Kishor Manohar Rao (Journal of Applied Pharmaceutical Science, 2019)
The aim of this study is to initiate the pharmacist–psychiatrist collaborative patient education in ambulatory care settings. A prospective cohort study was conducted in psychiatry out-patient department of a tertiary care teaching hospital over a period of 6 months. All the eligible patients were enrolled, and the necessary information was collected. The collected data were analyzed for medication adherence by using medication adherence rating scale and health-related quality of life by using the World Health Organization Quality of Life questionnaire. Student t-test was used to analyze the results at p-value
Keywords: Quality of life, medication adherence, pharmacist– psychiatrist collaborative care, ambulatory care.